Crystallites and Electric Fields in Solid Ammonia. Issue 10 (16th July 2020) - Cassidy, Andrew; James, Rachel L.; Dawes, Anita; Field, David
Abstract: Absorption spectra of vacuum‐deposited films of ammonia have been obtained in the range 115 nm to 310 nm for a set of 15 deposition temperatures, Td, between 20 K and 80 K. Results focus upon the region 115 nm to 130 nm in overlapping D, E, F and G←X Rydberg transitions involving Wannier‐Mott excitons. We identify two phases of ammonia, showing the solid to be polymorphic. Peak absorption wavelengths in the region of interest are found to shift to the red by 299 cm −1, for Td between 20 K to 50 K, and 1380 cm −1 for Td between 55 K to 80 K. Shifts provide evidence for the presence of spontaneously generated electric fields in these films, of values in excess of 10 8  V m −1 for Td of 20 K to 50 K to a few times 10 7  V m −1 for 55 K to 80 K. Results enable us to place a lower limit of 1.58 nm on the size of crystallites in the low temperature regime. This dimension represents 16 unit cells or 64 species, giving a more quantitative description than the nebulous term amorphous, as applied to solid ammonia. We also determine that crystallites formed in the high temperature regime contain, within ±20 %, 1688, 756 and 236 molecules of ammonia, respectively at Td of 65 K, 60 K and 55 K. Abstract : What do we mean when we describe a film of vacuum‐deposited material as amorphous and what by crystalline? In this study of spontaneously electrical solid ammonia, we show that the so‐called "amorphous" phase, prepared between 20–50 K, is a crystalline material composed of crystallites containing >64 molecules. More broadly, we introduce a technique to quantify the size of crystallites in nanoscale films.